British Medical Association complete home medical guide the essential reference for every family (Dorling Kindersley Limited, 2016)
The essential medical reference that's a must for every family, in a larger formatpublished in association with the bma, the new edition of this jargon-free, medical reference book gives you everything you need to make a major contribution to the present and future well-being of your family. From viral infections to immune disorders, find in-depth coverage of more than 750 medical conditions, including information on causes, symptoms, diagnosis, treatment, and prevention. There are easy-to-use symptom charts for self-diagnosis as well as detailed descriptions of medical tests and alternative treatments. Packed with up-to-date medical information every family needs to know and comprehensive coverage of every important aspect of health and medicine, this is a must for every home